Potential Plant Growth-Promoting Microorganism (PGPM) as Biological Control Agents of Paddy in Indonesia - Trisnani Alif; Mahindra Dewi Nur Aisyah (Journal of Soilscape and Agriculture, 2025)
Today, the main goal of agriculture is increasing crop yields to meet the ever-increasing human population. Climate change has increased the challenges associated with the cultivation of food crops, especially rice. It affects rice production due to the influence of biotic factors (Plant Pest Organisms) and an uncertain environment. To address this phenomenon, Plant Growth Promoting Microbial (PGPM) is considered a better alternative than using chemicals. It has been proven that Plant Growth Promoting Rhizobacteria (PGPR) and Fungi (PGPF) are effective in suppressing plant diseases and controlling pests by producing inhibitory chemicals and inducing immune responses in plants. Furthermore, PGPM increases growth and yields. As biofertilizers and biopesticides, PGPR and PGPF are considered attractive and economically viable approaches to the cultivation of rice in Indonesia. The potential for PGPM utilization is still high considering the diversity of microbes and the fact that these microbes can be found under a variety of environmental conditions. However, it is also a challenge to develop products, especially treatments to maintain the performance of the microbes that will be used